Beyond the visual: the lived experience of sensorimotor dissonance in virtual reality table tennis training - Novita Wulandari; Jusrianto As; Emayantii Anggraeni; Ninik Septyani; Mukharrar Fadjri (Jurnal Konseling dan Pendidikan, 2026)
This study explores the essence of table tennis athletes’ lived experiences when using a Virtual Reality (VR)–based forehand smash training model. Using a phenomenological approach, data were collected from provincial-level athletes through in-depth interviews, observation, and training documentation. The findings reveal a central experiential tension: while VR enhances cognitive engagement, decision-making, and technical awareness through immersive and feedback-rich environments, it simultaneously produces a sense of sensorimotor dissonance a mismatch between visual realism and the absence of authentic haptic and physical feedback. Athletes described this as a “different feel,” requiring continuous recalibration between virtual and real-world play. This duality positions VR not as a replacement for conventional training, but as a complementary tool that strengthens perceptual–cognitive aspects of performance while remaining limited in embodied sensory fidelity. These results highlight the importance of designing VR training systems that better integrate multisensory feedback and aligning their use within hybrid training models to optimize skill transfer and athlete experience.